Review of research on computer-assisted language learning with a focus on intercultural education - Shadiev, Rustam; Yu, Jiatian (Computer assisted language learning, 2024)
We reviewed articles on computer-assisted language learning, focusing on intercultural education studies published in the last five years. We investigated the following aspects: (1) the theoretical foundation that the studies were based on, e.g., theory, hypothesis, model, or framework, (2) the technologies used by the participants, (3) the languages and cultures that the studies focused on, (4) the methodology of the reviewed studies, and (5) the findings reported by researchers. Our results showed that Byram's intercultural communicative competence model, sociocultural theory, and social constructivism were the most frequently used theoretical foundations. The participants frequently used discussion forums, Facebook, email, and Skype. English was the most popular language, and American culture received more attention than any other culture. In terms of the methodology, most studies were conducted for four to 18 weeks, and undergraduate students with advanced language skills were the most frequent participants. The participants interacted with their partners, e.g., introduced cultural backgrounds, created collaborative products, and reflected on learning experiences. Researchers in most studies used questionnaires and interviews to collect the data, and their results demonstrated that intercultural telecollaboration in foreign language education promotes language and culture learning. Benefits such as students having positive attitudes toward technology-supported learning activities and learning activities contributing to developing language abilities and intercultural skills were reported by the researchers. However, according to the results, high cost and learning burdens were the most frequently reported drawbacks of CALL for intercultural education. Several implications were drawn from the results of this review study. The significance of this study is that it provides up-to-date information on CALL-based intercultural education, keeps track of changes in technologies and their applications to language and culture learning, and focuses on aspects that are important to the field but were neglected in earlier review studies.